2008
DOI: 10.5507/bp.2008.047
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Smoking and Its Effect on Arterial Stiffness

Abstract: Aims:The goal of this study was to investigate the eff ect of chronic smoking on arterial stiff ness at a peripheral site using pulse wave analysis.Methods: Forty two non-smokers (17 males, 25 females) of average age 20.2 ± 1.3 year and forty fi ve smokers (19 males, 26 females) of average age 24.3 ± 2.4 year were included in the study. Four parameters, SI (stiff ness index), RI (refl ection index), CT (crest time) and IWD (interwave distance) were evaluated by means of an adapted device based on pletysmograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…In one study, brPWV was significantly increased in smokers; 36 another study reported higher PWV in smokers, but did not report the arterial segment that was measured. 37 Similarly, increases in aortic stiffness were also noted in smokers in other studies. 38,39 In fact, cigarette smoking was found to be a significant predictor of increased aortic PWV in White and Black individuals (R 2 ¼0.13 and R 2 ¼0.14, respectively; Po0.05).…”
Section: Chronic Smokingsupporting
confidence: 51%
See 1 more Smart Citation
“…In one study, brPWV was significantly increased in smokers; 36 another study reported higher PWV in smokers, but did not report the arterial segment that was measured. 37 Similarly, increases in aortic stiffness were also noted in smokers in other studies. 38,39 In fact, cigarette smoking was found to be a significant predictor of increased aortic PWV in White and Black individuals (R 2 ¼0.13 and R 2 ¼0.14, respectively; Po0.05).…”
Section: Chronic Smokingsupporting
confidence: 51%
“…Most studies found that chronic smoking increases arterial stiffness as measured by PWV, AIx, SI, compliance and distensibility. 24,[36][37][38][39][47][48][49][50][51][52][53]63 However, a few other studies did not consistently find this effect. 32,[40][41][42] For example, Filipovsky et al 41 and Rehill et al 42 found that AIx was significantly higher in smokers than in nonsmokers, while differences in PWV did not reach significance.…”
Section: Discussionmentioning
confidence: 99%
“…Jatoi et al [21] described a significantly positive relationship between smoking status and PWV in 554 never-treated patients with essential hypertension. Also, two recent studies have reported that cigarette smoking increased baPWV in healthy young people [22,23], but others [24,25] found no difference in pulse wave velocity between smokers and non-smokers. We have observed that in normoglycaemic subjects, current smokers had greater baPWV adjusting for age, blood pressure and hsCRP.…”
Section: Discussionmentioning
confidence: 99%
“…Even though tobacco smoking is a well documented risk factor for CVD, its association with hypertension remains a paradox [2]. Smoking is associated with chronic low-grade inflammation [3] and arterial stiffness [4,5], which are associated with hypertension [6]. Carefully controlled experiments in healthy humans have shown that smoking causes an acute increase of blood pressure [4,7], and that smoking cessation reduces blood pressure, heart rate, and plasma epinephrine and norepinephrine concentrations among smokers [8].…”
Section: Introductionmentioning
confidence: 97%